Inpatient Physiotherapy for Functional (Psychogenic) Gait Disorder: A Case Series of 35 Patients. Issue 6 (29th January 2016) - Matthews, Audrey; Brown, Melanie; Stone, Jon
Abstract: View Supplementary Video 1 Patients with functional gait disorder (FGD) are often referred for physiotherapy, but data on their outcome is limited. The authors present a case series of 35 patients who received targeted physiotherapy for FGD at a regional neuroscience center (mean number of sessions, 11). Significant improvements in the Modified Rivermead Mobility Index (score range, 0–40) were recorded between pretreatment and posttreatment (mean pretreatment vs. posttreatment score, 20 vs. 37, respectively). Improvements also were seen in patients who had chronic symptoms, including those with symptom duration over 6 months (mean pretreatment vs. posttreatment score, 21 vs. 33, respectively) and in patients who had no psychological intervention. These data support the hypothesis that specific physiotherapy for FGD can be surprisingly effective and further encourage the development of larger randomized trials to test efficacy. Abstract : View Supplementary Video 1